Continuous Heart Rate Monitoring for Automatic Detection of Life-Threatening Arrhythmias With Novel Bio-Sensing Technology - Chorin, Ehud; Hochstadt, Aviram; Schwartz, Arie Lorin; Matz, Gil; Viskin, Sami; Rosso, Raphael (Frontiers in Cardiovascular Medicine, 2021)
Aims: Assessing the effectiveness of novel bio-sensing technology (CardiacSense), for accuracy and reliability of automatic detection of life-threatening arrhythmias. Methods and Results: This prospective study consisted of Eighteen patients (13 males and 5 females, mean age 59.4 ± 21.3 years) undergoing induction of ventricular tachycardia/fibrillation or provocation of transient ventricular asystole. We tested the detection of provoked ventricular arrhythmias by a wrist-worn watch-like device which uses photoplethysmography (PPG) technology to detect the cardiac rhythm. We used simultaneous electrocardiographic (ECG) recordings as gold standard for arrhythmia definition and confirmation of beat-to-beat detection. A total of 1,527 QRS complexes were recorded simultaneously by ECG and PPG. The overall correlation between the ECG (R-R intervals) and the PPG (G-G intervals) was high, with a correlation coefficient of R = 0.949 (p < 0.001). The device accurately detected all events of mimicked life endangering arrhythmias, including five events of transient (adenosine-induced) ventricular asystole as well as seven episodes of monomorphic ventricular tachycardia and 6 events of ventricular fibrillation. Conclusion: This proof-of-concept study suggests that wearable devices using PPG technology, currently used to detect atrial fibrillation, may also have a role as automatic detectors of life-threatening arrhythmias.